COVID-19 vaccine hesitancy among persons living in homeless shelters in France. Issue 25 (8th June 2021) - Longchamps, C.; Ducarroz, S.; Crouzet, L.; Vignier, N.; Pourtau, L.; Allaire, C.; Colleville, A.C.; El Aarbaoui, T.; Melchior, M.; ,
Abstract: COVID-19 vaccine hesitancy is frequent and can constitute a barrier to the dissemination of vaccines once they are available. Unequal access to vaccines may also contribute to socioeconomic inequalities with regard to COVID-19. We studied vaccine hesitancy among persons living in homeless shelters in France between May and June 2020 (n = 235). Overall, 40.9% of study participants reported vaccine hesitancy, which is comparable to general population trends in France. In multivariate regression models, factors associated with vaccine hesitancy are: being a woman (OR = 2.55; 95% CI 1.40–4.74), living with a partner (OR = 2.48, 95% CI 1.17–5.41), no legal residence in France (OR = 0.51, 95% CI 0.27–0.92), and health literacy (OR = 0.38, 95% CI 0.21, 0.68). Our results suggest that trends in vaccine hesitancy and associated factors are similar among homeless persons as in the general population. Dissemination of information on vaccine risks and benefits needs to be adapted to persons who experience severe disadvantage.